Global caregiver perspectives on COVID-19 immunization in childhood cancer: A qualitative study - Silverstein, Allison; Gumy, Julia M.; Bate, Jessica; Kaye, Erica C. (Frontiers in Public Health, 2023)
This study explores global caregiver’s perspectives related to COVID-19 immunization in the context of pediatric cancer management. A mixed methods survey was developed based on consensus questions with iterative feedback from global medical professional and caregiver groups and distributed globally to caregivers of childhood cancer via electronic and paper routes. We present qualitative findings through inductive content analysis of caregiver free-text responses. A total of 184 participants provided qualitative responses, 29.3% of total survey respondents, with a total of 271 codes applied. Codes focused on themes related to safety and effectiveness (n=95, 35.1%), logistics (n=69, 25.5%), statements supporting or opposing vaccination (n=55, 20.3%), and statements discussing the limited availability of information (n=31, 11.4%). Within the theme of safety and effectiveness, safety itself was the most commonly used code (n=66, 24.4% of total segments and 69.5% of safety and effectiveness codes), followed by risks versus benefits (n=18, 18.9% of safety and effectiveness codes) and efficacy (n=11, 11.6%). This study provides insights to guide healthcare professionals and caregiver peers in supporting families during the complex decision-making process for COVID-19 vaccination. These findings highlight the multidimensionality of concerns and considerations of caregivers of children with cancer regarding COVID-19 vaccination and suggest that certain perspectives transcend borders and cultures.